Qualitative analysis for single-phase grid-tie power inverter structures - Alves, Marcos G. [UNESP]; Brito, Moacyr A. G. de; Sampaio, Leonardo P.; Melo, Guilherme A. [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2014)
This paper presents comparisons among non-isolated DC to AC double-stage single-phase structures, including one integrated single-stage, for photovoltaic (PV) distributed generation applications, and suitable to operate connected to the AC power distribution network. Considering the ideal application for PVs this paper has focused on converters with natural characteristic of current source as input, which decreases the capacitance required for PV power decoupling. Simulation results and qualitative analysis are presented related to the power stage structures and experimental results of an application are discussed in order to confirm the feasibility of the proposal. The developed prototype is digitally controlled by a DSC, considering the designed firmware for MPPT (P&O), and in agreement with IEC and Brazilian standards for island and electrical protections.
Keywords: Single-phase solar inverters; Photovoltaic energy; MPPT; Islanding protection; Distributed generation